AN ERROR ANALYSIS ON THE STUDENTS’ WRITING DESCRIPTIVE TEXT AT VIII GRADE SMP NEGERI 2 LEIDONG - Desia Rahelia Putri Sihotang; Asima Rohana Sinaga; David Togi Hutahaean (RADJA PUBLIKA, 2025)
This study aimed to analyze grammatical errors made by eighth-grade students in writing descriptive texts, with a particular focus on the use of the simple present tense. The research employed a descriptive qualitative design. The participants were students of SMP Negeri 2 Kualuh Leidong, selected through purposive sampling. Data were collected using a writing test in which students were required to compose a descriptive text in English. The students’ written works were analyzed using surface strategy taxonomy, which classifies errors into omission, addition, misformation, and misordering. The analysis procedure involved identifying errors, categorizing them into the four types, and interpreting the results to determine dominant error patterns. The findings revealed that students produced various grammatical errors, with misformation and omission appearing as the most frequent types. These errors mainly occurred in subject–verb agreement, verb forms, and the use of auxiliary verbs in the simple present tense. The results indicate that students still have limited mastery of basic grammatical structures in descriptive writing. This study suggests that teachers should provide more focused grammar instruction and writing practice to help students reduce errors and improve their ability to write descriptive texts accurately.